High-hardness corrosion-resistant steel for structure and preparation process of high-hardness corrosion-resistant steel
By performing low-carbon, manganese-containing composite microalloying treatment on the automotive beam steel and forming a composite coating on the surface, the problem of steel being easily corroded in the natural environment is solved, and high hardness and corrosion resistance are improved.
Patent Information
- Application Number
- CN202411440453.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The steel used in automobile beams is prone to corrosion in the natural environment, resulting in a shortening of its life and insufficient corrosion resistance of the existing galvanized layer.
Low-carbon and manganese-containing steel billets are used to form composite microalloys through rolling, heat treatment and surface treatment processes, and elements such as titanium, niobium, molybdenum, vanadium and other elements are added for composite microalloys, and powder spraying and hot-dip galvanizing on the surface of the steel coil to form a composite coating containing boronide and zinc layer.
It significantly improves the hardness, corrosion resistance and mechanical properties of the steel, extends the service life, and improves the sensitivity to notch.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural steel, in particular to a high-hardness corrosion-resistant steel material for structure and a preparation process thereof. Background Art
[0002] The automobile beam is a major component of the automobile. It is supported on the wheels by the front and rear axles of the suspension device and bears almost the entire weight of the vehicle and its load. Its performance directly affects the service life and driving safety of the entire vehicle. The steel used in the automobile beam has a weak point in application, that is, it is easily corroded in contact with air in the natural environment. Without certain protective measures, its life will be greatly shortened. In the actual production of automobile beams, a galvanized layer is often used as a means of corrosion resistance. However, the hot-dip zinc layer on the surface of the steel will produce loose intermetallic compounds with the steel matrix, affecting its hardness and corrosion resistance. Therefore, we propose a high-hardness corrosion-resistant steel for structure and its preparation process. Summary of the invention
[0003] The object of the present invention is to provide a high-hardness corrosion-resistant steel material for structure and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A high-hardness corrosion-resistant steel material for structure is obtained by rolling, heat treatment and surface treatment of a steel billet;
[0005] Furthermore, the steel billet includes the following components: in mass percentage, carbon C: 0.05-0.09%, silicon Si: 0.05-0.12%, manganese Mn: 1.35-1.60%, aluminum Al: 0.02-0.05%, titanium Ti: 0.04-0.11%, niobium Nb: 0.03-0.05%, molybdenum Mo: 0.15-0.18%, vanadium V: 0.004-0.09%, boron B: ≤0.002%, phosphorus P: ≤0.015%, sulfur S: ≤0.005%, nitrogen N: ≤0.006%, oxygen O: ≤0.003%, and the balance is iron Fe.
[0006] Furthermore, in terms of mass percentage, in the steel billet composition, Nb+Ti: ≤0.14%; Nb+V+Ti: ≤0.22%; V+B: ≤0.09%.
[0007] In the above technical solution, the composition of the steel billet is characterized by low carbon and manganese, and is compositely micro-alloyed with elements such as titanium, niobium, molybdenum, and vanadium. Among them, titanium has a strong affinity with carbon and nitrogen in the steel billet, and has a low solubility in steel, which can affect the deformation and recrystallization process of austenite and achieve microstructure refinement; and can act as a deformation agent for sulfides in steel to further improve the mechanical properties and anisotropy of the steel billet.
[0008] Niobium also has excellent affinity with carbon and nitrogen, and can form fine carbonitrides, effectively inhibiting the recrystallization process and grain growth; compared with vanadium and titanium, niobium is more effective in inhibiting austenite growth and recrystallization. During the phase transformation process, the precipitation of niobium increases the nucleation rate of ferrite and improves the strength of the steel billet, achieving the fine grain strengthening and precipitation strengthening effects of the element niobium.
[0009] When niobium and titanium are added together, the amount of niobium added can be reduced to reduce costs, but a high titanium content will cause the precipitation of titanium-rich phases, which are coarse in size and detrimental to the overall performance of the steel billet. Therefore, the content of niobium and titanium is controlled to promote the precipitation of niobium and titanium carbonitrides in a small size and uniform distribution to prevent damage caused by stress concentration during deformation.
[0010] Vanadium can play a role in solid solution, segregation and precipitation in the steel billet, interact with carbon and nitrogen elements, and exist in the steel billet matrix and grain boundaries in the form of carbonitrides, which has the effect of precipitation strengthening, inhibiting grain growth, and inhibiting austenite recrystallization. Compared with niobium and titanium, vanadium has a higher solubility in austenite, less precipitation of carbonitrides, and the solid solution of vanadium is retained in austenite and precipitated in the subsequent rolling process, which has the effect of precipitation strengthening.
[0011] Niobium carbon and nitride can dissolve in high-temperature austenite and precipitate in low-temperature austenite, hindering the growth of the original austenite. Vanadium carbon and nitride dissolve in austenite and precipitate during or after the phase transformation. The precipitated carbonitride is relatively small and can pin the austenite grain boundary, making the ferrite grains after the phase transformation fine, reflecting the composite microalloying effect of niobium and vanadium in the steel billet.
[0012] Boron has a strong affinity with nitrogen and oxygen, and can combine with sulfur and carbon, and can also form substitutional solid solutions or interstitial solid solutions with iron. Boron preferentially segregates at grain boundaries, which can reduce the segregation of impurity elements sulfur and phosphorus at grain boundaries, alleviate the intergranular fracture caused by them, and is conducive to the improvement of grain boundary bonding in the steel billet; and can be adsorbed on the surface of sulfides and oxides to prevent their growth, make them refined and evenly distributed, alleviate local stress concentration and crack propagation, and effectively improve the toughness of the steel billet. Boron and vanadium composite can enhance the drag of niobium on condensation, reduce the interface migration speed and recrystallization driving force, further refine the grains, and help improve its hardenability, impact toughness, high temperature strength and creep properties. If the boron content in the steel is high, it will cause continuous deposition of boron at the grain boundaries, reducing the impact toughness of the steel billet.
[0013] The composite addition of vanadium and boron improves the stability of austenite, increases the starting temperature of ferrite transformation, delays phase transformation, and helps to obtain high-strength bainite structure after rolling, so that the produced steel coil has higher hardness.
[0014] The addition of molybdenum can increase the solubility of niobium carbonitride in austenite, allowing more molybdenum to remain in the solid solution, promoting its dispersion and precipitation during low-temperature transformation, and playing a better strengthening role. Molybdenum can increase the nucleation position of carbides, promote the refinement and increase of carbides; and help improve the corrosion resistance of steel billets.
[0015] A preparation process of high-hardness corrosion-resistant steel for structure, comprising the following processes:
[0016] The steel billet is rolled, heat treated and surface treated in sequence to obtain high-hardness corrosion-resistant steel.
[0017] Furthermore, the thickness of the steel billet is 32-55 mm.
[0018] Further, the rolling process is as follows: heating the steel billet to 1230-1270°C and keeping the temperature for 60 minutes; the rough rolling start temperature is 1130-1160°C and the final rolling temperature is 860-880°C; the number of passes is 5-8, and the first pass reduction is 13-16%;
[0019] Then, the steel is cooled to 600-630°C at a cooling rate of 18-25°C / s and coiled to obtain a steel coil.
[0020] Furthermore, the thickness of the steel coil is 2 to 6 mm.
[0021] In the above technical solution, the steel billet is rolled to prepare the steel coil. During the hot rolling and cooling process, stress deformation and high temperature rapid cooling transformation are used to promote phase transformation in the steel structure. Bainite and ferrite are formed in the austenite, and carbon is discharged into the austenite.
[0022] The steel billet structure forms high-density dislocations, and a fine dislocation cellular structure is formed during relaxation. Niobium, titanium and other elements are precipitated in the above structure under strain induction, and molybdenum has a certain refinement effect on the precipitates, producing a large number of nucleation sites, promoting the formation of bainite in the steel billet, and dividing and refining the deformed austenite grains. Molybdenum can increase the austenite transformation temperature, reduce the austenite phase area, expand the bainite phase area, and promote the formation of bainite; while the refined grains inhibit phase transformation and refine the structure to a certain extent, thereby achieving the precipitation and refinement of acicular ferrite and bainite in the steel coil structure, playing a phase transformation strengthening role, and improving the mechanical properties of the steel coil.
[0023] Furthermore, the heat treatment process is as follows: the heat treatment temperature is 450-600° C., and the insulation time is 135-180 minutes.
[0024] In the above technical solution, the steel coil is tempered after hot rolling to eliminate the residual stress in the steel coil and stabilize the matrix structure. At the heat treatment temperature, carbon and nitrides of alloying elements such as titanium and niobium are precipitated, and the number of precipitates increases, which plays a precipitation strengthening role; and as the tempering temperature increases, the particle size of the alloying element carbon and nitride gradually decreases, and the mechanical properties of the steel coil are improved. If the tempering temperature is too high, the precipitates will coarsen and grow, which is not conducive to improving the performance of the steel coil.
[0025] Furthermore, the surface treatment includes powder spraying and hot-dip galvanizing.
[0026] Furthermore, the process conditions for powder spraying are: air flow rate 88-90 L / min, propane flow rate 80-85 L / min, hydrogen flow rate 33-38 L / min, and nitrogen flow rate 28-32 L / min;
[0027] The spraying distance is 20 cm, the spraying angle is 90°, the powder feeding speed is 45-60 g / min, and the spraying speed is 800-1000 mm / s.
[0028] Furthermore, the spraying powder is obtained by mixing boride powder, cobalt powder, iron powder, polyethylene glycol and anhydrous ethanol, ball milling, vacuum drying and sintering.
[0029] Further, the mass ratio of boride powder, cobalt powder and iron powder is (66.9-84.4):(8-17):(7.6-16.1);
[0030] Polyethylene glycol is 1% of the total mass of boride powder, cobalt powder and iron powder;
[0031] The total volume of anhydrous ethanol, boride powder, cobalt powder and iron powder is the same.
[0032] Furthermore, the process conditions of ball milling are: rotation speed 200-240 r / min, duration 8-10 h;
[0033] The process conditions of vacuum drying are: temperature 75-80°C, duration 8-10h;
[0034] The sintering process conditions are: heating to 300-320°C at a heating rate of 1-2°C / min, keeping warm for 60-80min; heating to 420-430°C, keeping warm for 60-80min;
[0035] Raise the temperature to 1160-1180°C at a heating rate of 9-10°C / min, and keep warm for 120-130 minutes; raise the temperature to 1250-1270°C, and keep warm for 150-160 minutes;
[0036] After sintering, the product is crushed, ground and sieved to retain the powder with a particle size of 37 to 48 μm.
[0037] Further, the boride powder is prepared by the following process:
[0038] The chromium boride and aluminum powder are mixed, anhydrous ethanol is added, ball-milled, dried, passed through a 120-mesh sieve, pressed into blocks, and sintered to obtain the product.
[0039] Further, the mass ratio of chromium boride to aluminum powder is 10:(2.5-6.5);
[0040] The total volume of anhydrous ethanol, chromium boride and aluminum powder is the same.
[0041] Furthermore, the process conditions of ball milling are: rotation speed 300-400 rpm, duration 4-6 h;
[0042] Drying temperature is 40-50°C;
[0043] The process conditions of briquetting are: applying pressure of 80-100 MPa and maintaining pressure for 10-15 minutes;
[0044] The sintering process conditions are: under the protection of nitrogen atmosphere, heating to 950-1000°C at a heating rate of 9-10°C / min, keeping the temperature for 180-200min, and cooling with the furnace;
[0045] After sintering, the product is crushed, ground and sieved to retain the powder with a particle size of 37 to 48 μm.
[0046] Further, the hot dip galvanizing process is as follows:
[0047] The steel coil obtained after powder spraying is heated to 460-480°C, sent into zinc liquid, hot-dip plated for 3-5 seconds, pulled out, purged with nitrogen, and cooled to room temperature at a cooling rate of 100°C / s to obtain a coating.
[0048] Further, the temperature of the zinc solution is 450-460°C;
[0049] The zinc liquid includes the following components: in percentage by mass, silicon Si: 0.1-0.5%, aluminum Al: 4.0-8.0%, and the balance is zinc Zn.
[0050] In the above technical scheme, during hot-dip galvanizing, complex physical and chemical reactions will occur between the steel surface and the aluminum melt, and the zinc atoms and iron atoms will combine to form a hard and brittle intermetallic compound (Γ phase), which can effectively prevent the zinc liquid from dissolving and further penetrating the steel matrix, and slow down the diffusion process. Iron atoms and zinc atoms diffuse in the Γ phase to form a δ phase, which is strong and has toughness and ductility. There are certain pores in the δ phase, which accelerates the diffusion of zinc atoms and reacts with the δ phase to form a ζ phase. The ζ phase is bundle-shaped and relatively loose. It is easy to fall off and peel off under the scouring of thermal convection and zinc liquid. Therefore, the present application performs powder spraying on the steel coil before hot-dip galvanizing. The spraying powder contains boride, which is sprayed at high speed to impact the steel coil, and the surface of the steel coil is ceramicized, which can significantly improve the surface hardness, thermal stability, corrosion resistance, wear resistance and other properties of the steel coil. Cobalt can form a continuous solid solution with iron to form a soft and tough phase, thereby improving the bonding ability between the coating and the steel coil; and it helps to improve the adhesion of the coating on the surface of the steel coil. Boride is prepared from chromium boride and aluminum powder. Aluminum is introduced into chromium boride through sintering to form Cr-Al-B powder, which reduces the brittleness of the boride. The steel produced can achieve high surface hardness and high strength while obtaining good toughness and modulus; it also helps to obtain better corrosion resistance. The coating on the surface of the steel can reduce its notch sensitivity and help improve its notch impact performance.
[0051] During hot-dip galvanizing, the spray powder is compounded with the zinc liquid, and the zinc liquid forms a metallic bond with elements such as iron and cobalt to form an intermediate layer, which can effectively improve the surface hardness and corrosion resistance of the steel. In addition, it is difficult for the zinc liquid to diffuse on the coating surface, which can effectively reduce the generation of loose iron-aluminum phases. The aluminum in the zinc liquid can significantly improve the surface corrosion resistance of the steel, while excessive aluminum will cause excessive brittle Fe-Al compounds on the surface of the steel, affecting the bonding between the coating and the steel coil. The small amount of silicon contained in the zinc liquid can inhibit the growth of Fe-Al compounds and improve the bonding between the plating solution and the steel coil.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] 1. The high-hardness corrosion-resistant steel for structure described in the present invention is based on low-carbon, manganese-containing steel and is compositely micro-alloyed with elements such as niobium, titanium, vanadium, and boron to improve the mechanical properties and corrosion resistance of the steel.
[0054] 2. The high-hardness corrosion-resistant steel for structure described in the present invention is powder-sprayed and hot-dip galvanized on the steel coils obtained after hot rolling and tempering, and a boride-containing coating and a zinc layer are provided on the surface of the steel coils to improve the surface hardness and corrosion resistance of the steel, and help improve the sensitivity of the steel to notches. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] In the following specific implementation, the thickness of the steel billet is 32 mm; the thickness of the steel coil is 5 mm;
[0057] Chromium boride: average particle size 1.8 μm, purity > 98.5%, sourced from Beijing Zhongke Jinyan Technology Co., Ltd.
[0058] Aluminum powder: particle size 300 mesh, from Beikuang New Material Technology Co., Ltd.;
[0059] Cobalt powder: average particle size 2.3 μm, purity 99.8%, sourced from Nanjing Hanrui Cobalt Co., Ltd.
[0060] Iron powder: average particle size 5μm, sourced from China Science and Technology Research (Beijing) Technology Co., Ltd.
[0061] Embodiment 1: A process for preparing a high-hardness corrosion-resistant steel material for structure, comprising the following processes:
[0062] Step 1, rolling: heating the steel billet to 1230°C and keeping it warm for 60 minutes; the rough rolling start temperature is 1130°C and the final rolling temperature is 860°C; the number of passes is 8, and the first pass reduction is 13%; then cooling to 600°C at a cooling rate of 18°C / s, coiling; keeping it warm at a tempering temperature of 450°C for 135 minutes to obtain a steel coil;
[0063] The steel billet comprises the following components: by mass percentage, C: 0.08%, Si: 0.07%, Mn: 1.38%, Al: 0.03%, Ti: 0.08%, Nb: 0.03%, Mo: 0.17%, V: 0.07%, B: 0.0017%, P: 0.010%, S: 0.002%, N: 0.003%, O: 0.001%, and the balance is Fe;
[0064] Step 2: Surface treatment:
[0065] (1) Powder coating:
[0066] Mix chromium boride and aluminum powder in a mass ratio of 10:2.5, add anhydrous ethanol; ball mill at a speed of 300rpm for 6h; dry at 40℃ and pass through a 120-mesh sieve; apply a pressure of 80MPa and maintain the pressure for 15min to form a cylindrical compact with a diameter of 50mm; sinter: under the protection of nitrogen atmosphere, heat to 950℃ at a heating rate of 9℃ / min, keep the temperature for 180min, and cool with the furnace; after sintering, crush, grind and sieve to retain the powder with a particle size of 37-48μm to obtain boride powder; the total volume of anhydrous ethanol, chromium boride and aluminum powder is the same;
[0067] The boride powder, cobalt powder and iron powder with a mass ratio of 84.4:8:7.6 were mixed, polyethylene glycol and anhydrous ethanol were added, and the mixture was ball-milled at a speed of 200 r / min for 10 hours; vacuum dried at 75°C for 10 hours, and sintered. The sintering process conditions were as follows: heating to 300°C at a heating rate of 1°C / min, and keeping the temperature for 60 minutes; heating to 420°C, and keeping the temperature for 60 minutes; heating to 1160°C at a heating rate of 9°C / min, and keeping the temperature for 120 minutes; heating to 1250°C, and keeping the temperature for 150 minutes; after sintering, the mixture was crushed, ground, and sieved to retain the powder with a particle size of 37 to 48 μm to obtain a spray powder; polyethylene glycol was 1% of the total mass of the boride powder, cobalt powder and iron powder; the total volume of anhydrous ethanol was the same as that of the boride powder, cobalt powder and iron powder;
[0068] The powder was sprayed on the surface of the steel coil under the following process conditions: air flow rate 89 L / min, propane flow rate 82 L / min, hydrogen flow rate 35 L / min, nitrogen flow rate 30 L / min; spraying distance 20 cm, spraying angle 90°, powder feed rate 45 g / min, spraying speed 800 mm / s; a coating was formed;
[0069] (2) Hot dip galvanizing:
[0070] The steel coil obtained after powder spraying is heated to 460°C, sent into a 450°C zinc liquid, hot-dip plated for 4s, pulled out, purged with nitrogen, and cooled to room temperature at a cooling rate of 100°C / s to form a coating to obtain a high-hardness corrosion-resistant steel; the zinc liquid includes the following components: in mass percentage, Si: 0.2%, Al: 4.1%, and the balance is Zn.
[0071] Embodiment 2: A process for preparing a high-hardness corrosion-resistant steel material for structure, comprising the following processes:
[0072] Step 1, rolling: heating the steel billet to 1250°C and keeping it warm for 60 minutes; the rough rolling start temperature is 1145°C and the final rolling temperature is 870°C; the number of passes is 8, and the first pass reduction is 15%; then cooling to 615°C at a cooling rate of 20°C / s, coiling; keeping it warm for 160 minutes at a tempering temperature of 525°C to obtain a steel coil;
[0073] The steel billet comprises the following components: by mass percentage, C: 0.08%, Si: 0.07%, Mn: 1.38%, Al: 0.03%, Ti: 0.08%, Nb: 0.03%, Mo: 0.17%, V: 0.07%, B: 0.0017%, P: 0.010%, S: 0.002%, N: 0.003%, O: 0.001%, and the balance is Fe;
[0074] Step 2: Surface treatment:
[0075] (1) Powder coating:
[0076] Mix chromium boride and aluminum powder in a mass ratio of 10:4.5, add anhydrous ethanol; ball mill at a speed of 350rpm for 5h; dry at 45℃ and pass through a 120-mesh sieve; apply a pressure of 90MPa and maintain the pressure for 12min to form a cylindrical compact with a diameter of 50mm; sinter: under the protection of nitrogen atmosphere, heat to 980℃ at a heating rate of 9℃ / min, keep the temperature for 190min, and cool with the furnace; after sintering, crush, grind and sieve to retain the powder with a particle size of 37-48μm to obtain boride powder; the total volume of anhydrous ethanol, chromium boride and aluminum powder is the same;
[0077] The boride powder, cobalt powder and iron powder with a mass ratio of 76.2:12:11.8 were mixed, polyethylene glycol and anhydrous ethanol were added, and the mixture was ball-milled at a speed of 220 r / min for 9 hours; vacuum dried at 78°C for 9 hours, and sintered. The sintering process conditions were as follows: heating to 310°C at a heating rate of 1°C / min, and keeping the temperature for 70 minutes; heating to 425°C, and keeping the temperature for 70 minutes; heating to 1170°C at a heating rate of 9°C / min, and keeping the temperature for 125 minutes; heating to 1260°C, and keeping the temperature for 155 minutes; after sintering, the mixture was crushed, ground, and sieved to retain the powder with a particle size of 37 to 48 μm to obtain a spray powder; polyethylene glycol was 1% of the total mass of the boride powder, cobalt powder and iron powder; the total volume of anhydrous ethanol was the same as that of the boride powder, cobalt powder and iron powder;
[0078] The powder was sprayed on the surface of the steel coil under the following process conditions: air flow rate 89 L / min, propane flow rate 82 L / min, hydrogen flow rate 35 L / min, nitrogen flow rate 30 L / min; spraying distance 20 cm, spraying angle 90°, powder feed rate 50 g / min, spraying speed 900 mm / s; a coating was formed;
[0079] (2) Hot dip galvanizing:
[0080] The steel coil obtained after powder spraying is heated to 470°C, sent into a 455°C zinc liquid, hot-dip plated for 3 seconds, pulled out, purged with nitrogen, and cooled to room temperature at a cooling rate of 100°C / s to form a coating to obtain a high-hardness corrosion-resistant steel; the zinc liquid includes the following components: in mass percentage, Si: 0.3%, Al: 6.2%, and the balance is Zn.
[0081] Embodiment 3: A process for preparing a high-hardness corrosion-resistant steel material for structure, comprising the following processes:
[0082] Step 1, rolling: heating the steel billet to 1270°C and keeping it warm for 60 minutes; the rough rolling start temperature is 1160°C and the final rolling temperature is 880°C; the number of passes is 8, and the first pass reduction is 13%; then cooling to 630°C at a cooling rate of 25°C / s, coiling; keeping it warm for 180 minutes at a tempering temperature of 600°C to obtain a steel coil;
[0083] The steel billet comprises the following components: by mass percentage, C: 0.08%, Si: 0.07%, Mn: 1.38%, Al: 0.03%, Ti: 0.08%, Nb: 0.03%, Mo: 0.17%, V: 0.07%, B: 0.0017%, P: 0.010%, S: 0.002%, N: 0.003%, O: 0.001%, and the balance is Fe;
[0084] Step 2: Surface treatment:
[0085] (1) Powder coating:
[0086] Mix chromium boride and aluminum powder in a mass ratio of 10:6.5, add anhydrous ethanol; ball mill at a speed of 400rpm for 4h; dry at 50℃ and pass through a 120-mesh sieve; apply a pressure of 100MPa and maintain the pressure for 15min to form a cylindrical compact with a diameter of 50mm; sinter: under the protection of nitrogen atmosphere, heat to 1000℃ at a heating rate of 10℃ / min, keep the temperature for 200min, and cool with the furnace; after sintering, crush, grind and sieve to retain the powder with a particle size of 37-48μm to obtain boride powder; the total volume of anhydrous ethanol, chromium boride and aluminum powder is the same;
[0087] The boride powder, cobalt powder and iron powder with a mass ratio of 66.9:17:16.1 were mixed, polyethylene glycol and anhydrous ethanol were added, and the mixture was ball-milled at a speed of 240 r / min for 8 hours; vacuum dried at 80°C for 10 hours, and sintered. The sintering process conditions were as follows: heating to 320°C at a heating rate of 2°C / min, and keeping the temperature for 80 minutes; heating to 430°C, and keeping the temperature for 80 minutes; heating to 1180°C at a heating rate of 10°C / min, and keeping the temperature for 130 minutes; heating to 1270°C, and keeping the temperature for 160 minutes; after sintering, the mixture was crushed, ground, and sieved to retain the powder with a particle size of 37 to 48 μm to obtain a spray powder; polyethylene glycol was 1% of the total mass of the boride powder, cobalt powder and iron powder; the total volume of anhydrous ethanol was the same as that of the boride powder, cobalt powder and iron powder;
[0088] The coating was formed by spraying powder on the surface of the steel coil under the following process conditions: air flow rate 89 L / min, propane flow rate 82 L / min, hydrogen flow rate 35 L / min, nitrogen flow rate 30 L / min; spraying distance 20 cm, spraying angle 90°, powder feed rate 60 g / min, spraying speed 1000 mm / s;
[0089] (2) Hot dip galvanizing:
[0090] The steel coil obtained after powder spraying is heated to 480°C, sent into a 460°C zinc liquid, hot-dip plated for 5 seconds, pulled out, purged with nitrogen, and cooled to room temperature at a cooling rate of 100°C / s to form a coating to obtain a high-hardness corrosion-resistant steel; the zinc liquid includes the following components: in mass percentage, Si: 0.48%, Al: 7.8%, and the balance is Zn.
[0091] Comparative Example 1: A process for preparing a high-hardness corrosion-resistant steel for structure, comprising the following processes:
[0092] Step 1 is the same as in Example 1, obtaining a steel coil;
[0093] Step 2: Surface treatment: (1) Powder coating:
[0094] Mix chromium boride and aluminum powder in a mass ratio of 10:2.5, add anhydrous ethanol; ball mill at a speed of 300rpm for 6h; dry at 40℃ and pass through a 120-mesh sieve; apply a pressure of 80MPa and maintain the pressure for 15min to form a cylindrical compact with a diameter of 50mm; sinter: under the protection of nitrogen atmosphere, heat to 950℃ at a heating rate of 9℃ / min, keep the temperature for 180min, and cool with the furnace; after sintering, crush, grind and sieve to retain the powder with a particle size of 37-48μm to obtain boride powder; the total volume of anhydrous ethanol, chromium boride and aluminum powder is the same;
[0095] The boride powder and iron powder with a mass ratio of 91.7:8.3 were mixed, polyethylene glycol and anhydrous ethanol were added, and the mixture was ball-milled at a speed of 200 r / min for 10 hours; vacuum dried at 75°C for 10 hours, and sintered. The sintering process conditions were as follows: heating to 300°C at a heating rate of 1°C / min, and keeping the temperature for 60 minutes; heating to 420°C, and keeping the temperature for 60 minutes; heating to 1160°C at a heating rate of 9°C / min, and keeping the temperature for 120 minutes; heating to 1250°C, and keeping the temperature for 150 minutes; after sintering, the mixture was crushed, ground, and sieved to retain the powder with a particle size of 37 to 48 μm to obtain a spray powder; polyethylene glycol was 1% of the total mass of the boride powder and the iron powder; the total volume of anhydrous ethanol was the same as that of the boride powder and the iron powder;
[0096] The powder was sprayed on the surface of the steel coil under the following process conditions: air flow rate 89 L / min, propane flow rate 82 L / min, hydrogen flow rate 35 L / min, nitrogen flow rate 30 L / min; spraying distance 20 cm, spraying angle 90°, powder feed rate 45 g / min, spraying speed 800 mm / s; a coating was formed;
[0097] (2) Hot-dip galvanizing is performed in the same manner as in Example 1 to form a coating and obtain a high-hardness, corrosion-resistant steel material.
[0098] Comparative Example 2: A process for preparing a high-hardness corrosion-resistant steel for structure, comprising the following processes:
[0099] Step 1 is the same as in Example 1, obtaining a steel coil;
[0100] Step 2: Surface treatment: (1) Powder coating:
[0101] The chromium boride and iron powder are mixed in a mass ratio of 92.4:7.6, polyethylene glycol and anhydrous ethanol are added, and the mixture is ball-milled at a speed of 200 r / min for 10 hours; vacuum dried at 75°C for 10 hours, and sintered. The sintering process conditions are as follows: heating to 300°C at a heating rate of 1°C / min, and keeping the temperature for 60 minutes; heating to 420°C, and keeping the temperature for 60 minutes; heating to 1160°C at a heating rate of 9°C / min, and keeping the temperature for 120 minutes; heating to 1250°C, and keeping the temperature for 150 minutes; after sintering, the mixture is crushed, ground, and sieved to retain powder with a particle size of 37 to 48 μm to obtain a spray powder; the polyethylene glycol is 1% of the total mass of the chromium boride and iron powder; the total volume of anhydrous ethanol is the same as that of the chromium boride and iron powder;
[0102] The powder was sprayed on the surface of the steel coil under the following process conditions: air flow rate 89 L / min, propane flow rate 82 L / min, hydrogen flow rate 35 L / min, nitrogen flow rate 30 L / min; spraying distance 20 cm, spraying angle 90°, powder feed rate 45 g / min, spraying speed 800 mm / s; a coating was formed;
[0103] (2) Hot-dip galvanizing is performed in the same manner as in Example 1 to form a coating and obtain a high-hardness, corrosion-resistant steel material.
[0104] Comparative Example 3: A process for preparing a high-hardness corrosion-resistant steel for structure, comprising the following processes:
[0105] Step 1 is the same as in Example 1, obtaining a steel coil;
[0106] Step 2, hot dip galvanizing:
[0107] The steel coil obtained after powder spraying is heated to 460°C, sent into a 450°C zinc liquid, hot-dip plated for 4s, pulled out, purged with nitrogen, and cooled to room temperature at a cooling rate of 100°C / s to form a coating to obtain a high-hardness corrosion-resistant steel; the zinc liquid includes the following components: by mass percentage, Si: 0.2%, Al: 4.1%, chromium boride: 2.0%, and the balance Zn
[0108] Step 2: Hot-dip galvanizing is the same as in Example 1 to form a coating to obtain a high-hardness, corrosion-resistant steel.
[0109] Comparative Example 4: A process for preparing a high-hardness corrosion-resistant steel for structure, comprising the following processes:
[0110] The steel billet is heated to 1230°C and kept at this temperature for 60 minutes; the starting temperature of the rough rolling is 1130°C and the final rolling temperature is 860°C; the number of passes is 5 and the reduction of the first pass is 13%; then the steel billet is cooled to 600°C at a cooling rate of 18°C / s and coiled; the steel billet is tempered at 450°C and kept at this temperature for 135 minutes to obtain a steel coil;
[0111] The steel billet includes the following components: in mass percentage, C: 0.08%, Si: 0.07%, Mn: 1.45%, Al: 0.05%, Ti: 0.12%, Nb: 0.04%, Mo: 0.15%, P: 0.012%, S: 0.002%, N: 0.004%, O: 0.001%, and the balance is Fe.
[0112] Experiment: The steel coils and high-hardness corrosion-resistant steels obtained in Examples 1-3 and Comparative Examples 1-4 were taken to prepare samples, and their properties were tested and the test results were recorded:
[0113] Hardness test: GB / T 4340.1 is used as the reference standard to test the Vickers hardness of high-hardness corrosion-resistant steel samples (steel coil samples in Comparative Example 4); the load application time is 10s, and 8 different positions on the surface of the sample are tested, and the average value is taken as the test result;
[0114] Corrosion resistance test: The sample was placed in a salt spray chamber to test the corrosion resistance of the high hardness corrosion-resistant steel (the steel coil sample in Comparative Example 4). The temperature in the salt spray chamber was 35°C, the relative humidity was 90%, and the temperature was 100°C per 80 cm. 2 The salt spray deposition is 2.0 mL / h, and the salt spray is 5 wt% sodium chloride solution; observe the time when the sample appears red rust in the salt spray test.
[0115] Tensile performance test: GB / T 228.1 is used as the reference standard, and a tensile testing machine is used to test the yield strength and tensile strength of the steel coil sample; the tensile speed is 5mm / min;
[0116] Impact performance test: using standard Charpy V-notch specimens, the low-temperature impact energy of high-hardness corrosion-resistant steel specimens (the steel coil specimens in Comparative Example 4) was tested on a pendulum impact tester; the test temperature was -20°C.
[0117] Vickers hardness (HV) Yield strength (MPa) Tensile strength(MPa) Impact energy (J) Corrosion resistance time (h) Example 1 303 785 818 232 2500 Example 2 320 780 813 240 2700 Example 3 341 776 807 238 2800 Comparative Example 1 288 \ \ 184 2200 Comparative Example 2 326 \ \ 171 2100 Comparative Example 3 224 \ \ 152 1700 Comparative Example 4 280 745 806 120 96
[0118] According to the data in the above table, we can clearly draw the following conclusions:
[0119] The high hardness corrosion-resistant steel obtained in Examples 1-3 is compared with the high hardness corrosion-resistant steel obtained in Comparative Examples 1-3 and the steel coil obtained in Comparative Example 4. The test results show that:
[0120] Compared with the comparative example, the steel coils and high-hardness corrosion-resistant steels obtained in Examples 1-3 have higher Vickers hardness, yield strength, tensile strength, impact work and corrosion resistance time data, which fully demonstrates that the present invention achieves improvements in the mechanical properties of the steel coils, the impact toughness, surface hardness and corrosion resistance of the high-hardness corrosion-resistant steels.
[0121] Compared with Example 1, the spray powder in Comparative Example 1 is prepared from boride and iron powder; the spray powder in Comparative Example 2 is prepared from chromium boride and iron powder; the surface treatment process in Comparative Example 3 is hot-dip galvanizing, and the zinc liquid contains chromium boride. The high-hardness corrosion-resistant steels obtained in Comparative Examples 1-3 have different surface treatment processes, and their Vickers hardness, impact energy and corrosion resistance time data are relatively low. It can be seen that the setting of the steel surface treatment process and the components used in this application can promote the improvement of the notch sensitivity, surface hardness and corrosion resistance of the steel.
[0122] The high hardness corrosion-resistant steel obtained in Examples 1-3 is compared with the steel coil obtained in Comparative Example 4. The steel coil obtained in Comparative Example 4 has a different steel billet composition from that in Examples 1-3. The test results show that the steel coil obtained in Comparative Example 4 has lower yield strength and tensile strength. It can be seen that the setting of the steel billet composition in the present application is conducive to the improvement of its mechanical properties.
[0123] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0124] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-hardness corrosion-resistant steel material for structure, characterized in that: Obtained from steel billets through rolling, heat treatment and surface treatment; The steel billet comprises the following components: by mass percentage, C: 0.05-0.09%, Si: 0.05-0.12%, Mn: 1.35~1.60%, Al: 0.02~0.05%, Ti: 0.04~0.11%, Nb: 0.03~0.05%, Mo: 0.15~0.18%, V: 0.004~0.09%, B: ≤0.002%, P: ≤0.015%, S: ≤0.005%, N: ≤0.006%, O: ≤0.003%, and the balance is Fe.
2. The high-hardness corrosion-resistant steel material for structure according to claim 2, characterized in that: In terms of mass percentage, in the steel billet composition, Nb+Ti: ≤0.14%; Nb+V+Ti: ≤0.22%; V+B: ≤0.09%.
3. A process for preparing high-hardness corrosion-resistant steel for structure, characterized in that: Including the following processes: Heat the steel billet to 1230-1270°C and keep it warm for 60 minutes; The starting temperature of the rough rolling is 1130-1160°C, and the final rolling temperature is 860-880°C; the number of passes is 5-8, and the reduction of the first pass is 13-16%; Cooling to 600-630°C at a cooling rate of 18-25°C / s, coiling, and heat treating to obtain a steel coil; Then powder spraying and hot-dip galvanizing are carried out in sequence to obtain high-hardness and corrosion-resistant steel.
4. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 3, characterized in that: The process conditions of the heat treatment are: temperature 450-600° C., and insulation time 135-180 min.
5. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 3, characterized in that: The process conditions of the powder spraying are: air flow rate 88-90 L / min, propane flow rate 80-85 L / min, hydrogen flow rate 33-38 L / min, nitrogen flow rate 28-32 L / min; The spraying distance is 20 cm, the spraying angle is 90°, the powder feeding speed is 45-60 g / min, and the spraying speed is 800-1000 mm / s.
6. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 5, characterized in that: The spraying powder is obtained by mixing boride powder, cobalt powder, iron powder, polyethylene glycol and anhydrous ethanol, ball milling, vacuum drying and sintering.
7. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 6, characterized in that: The mass ratio of boride powder, cobalt powder and iron powder is (66.9-84.4):(8-17):(7.6-16.1).
8. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 6, characterized in that: The sintering process conditions are: heating to 300-320°C at a heating rate of 1-2°C / min, keeping the temperature for 60-80min; heating to 420-430°C, keeping the temperature for 60-80min; Raise the temperature to 1160-1180°C at a heating rate of 9-10°C / min, and keep warm for 120-130 minutes; raise the temperature to 1250-1270°C, and keep warm for 150-160 minutes; After sintering, the product is crushed, ground and sieved to retain the powder with a particle size of 37 to 48 μm.
9. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 7, characterized in that: The boride powder is prepared by the following process: Mix chromium boride and aluminum powder in a mass ratio of 10:(2.5-6.5), add anhydrous ethanol, ball-mill, dry, pass through a 120-mesh sieve, briquette, sinter, and after sintering, crush, grind, and sieve to retain powder with a particle size of 37-48 μm.
10. The process for preparing a high-hardness corrosion-resistant steel material for structure according to claim 9, characterized in that: The sintering process conditions are: under the protection of nitrogen atmosphere, heating to 950-1000° C. at a heating rate of 9-10° C. / min, keeping the temperature for 180-200 minutes, and cooling with the furnace.
Citation Information
Patent Citations
High-strength steel for 750 to 880 MPa-level vehicles and production method thereof
CN102363858A
Hot-rolled steel plate coil for thick-wall large-diameter ERW submarine pipeline and preparation method of hot-rolled steel plate coil
CN110241360A
Tensile strength 800-MPa-class hot rolling complex phase steel and production method thereof
CN110343961A
ERW submarine pipeline steel plate coil and production process thereof
CN110863145A
TMCP-process ultrahigh-strength steel with yield strength higher than 800 MPa and production method thereof
CN111647813A
Cited By
High-hardness compression-resistant alloy steel plate and preparation process thereof
CN120366776A